2020
DOI: 10.1016/j.ymgme.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on patients with Fabry disease: An Italian experience

Abstract: We conducted an observational study to assess the impact of COVID-19 emergency on management and outcomes of patients with Fabry disease referring to our Center in Naples, Italy. No patient of the 129 included reported suspected symptoms; 3 isolated themselves in auto-quarantine for flu-like symptoms. All treated patients regularly continued their therapies; 8 missed one infusion: 3 for self-isolation with 2 relatives, and 3 refused to receive nurse at home. All elective procedures were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 4 publications
4
18
0
Order By: Relevance
“…As might be expected and in line with recent reports [ 3 , [5] , [6] , [7] , [8] , [9] , 11 ], HCPs noted that there had been some interruptions to treatment because of the COVID-19 pandemic; 38.0%, 32.6%, and 15.2% of respondents noted that <1%, 1–10%, or > 10–20% of patients, respectively, had missed infusions. A small proportion of HCPs reported that patients had missed >20–50% or > 50% of infusions (4.3% and 5.4% of respondents, respectively).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As might be expected and in line with recent reports [ 3 , [5] , [6] , [7] , [8] , [9] , 11 ], HCPs noted that there had been some interruptions to treatment because of the COVID-19 pandemic; 38.0%, 32.6%, and 15.2% of respondents noted that <1%, 1–10%, or > 10–20% of patients, respectively, had missed infusions. A small proportion of HCPs reported that patients had missed >20–50% or > 50% of infusions (4.3% and 5.4% of respondents, respectively).…”
Section: Resultssupporting
confidence: 86%
“…Other factors noted by respondents as free text entries included psychiatric effects, stress and fear, access to vaccination, continued treatment, optimum care, disease surveillance and disease management, and access to school, social, and community services. The concerns noted by HCPs for their patients in this survey appear to align with the results of published patient surveys [ [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. Furthermore, most respondents were concerned that the risks associated with contracting COVID-19 for patients with LSDs may be higher than for the general population; 47.8% of respondents were ‘somewhat concerned’ and 34.8% of respondents were ‘greatly concerned’; however, 17.4% of respondents were ‘not concerned’ that risks may be higher in this patient population.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The results of our study confirm previous findings regarding the need for psychological support to reduce levels of stress and anxiety during a pandemic for patients with rare diseases and their families, as well as for providing remote counselling to the extent that, due to the specificity of the disease, it is possible [27][28][29]. Similar to the findings concerning patients with cystic fibrosis (CF) [29], our patients also reported changes in daily routine during self-isolation; this was mostly unintentional non-adherence to treatment for CF, whereas, in our study, most respondents' self-reported adherence was better, though some reported poor adherence or complete non-adherence to their diet.…”
Section: Discussionsupporting
confidence: 89%
“…There was also at least a theoretical concern that patients with Gaucher disease might be especially at risk if early Sars-CoV-2 treatments like hydroxychloroquine, that could disrupt autophagy needed to maintain homeostasis, were administered. In response to this call to action, both patient groups and physician investigators have attempted to educate and to survey the Gaucher patient population to assess the evolving impact of the Sars-CoV-2 disease and pandemic on their care and health [ 3 , 5 , 9 , 10 ]).…”
mentioning
confidence: 99%